Productivity and Economics of Free Ranging Desi Poultry In Sugarcane Integrated Farming System - M. Mohamed Amanullah, T. Ananthi, (International Journal of Scientific Research and Management (IJSRM), 2017)
A field experiment was conducted at farmers field, Coimbatore during kharif 2016 -17 to analyse the productivity and economics of free ranging desi poultry  in sugarcane integrated farming system. The popular sugarcane variety Mandya and local breeds of desi poultry were used for this study. Two farming systems viz., Sugarcane alone; Sugarcane + desi poultry (2 hens and 1 rooster for 3 cents) were evaluated under field conditions. The sugarcane + desi poultry recorded higher cane yield than sugarcane under sole crop.  The increase in yield under sugarcane + desi bird farming system was negligible when compared to cane yield of sole sugarcane. The treatment combination of sugarcane with desi bird recorded higher gross return, net return and benefit cost ratio through selling of eggs and birds in addition to sugarcane yield